Desempenho agronômico de cultivares de feijão-caupi inoculadas com rizóbio no semiárido brasileiro - Oliveira, Pedro Ramon Holanda de (2020)
The Northeast region is the main producer and consumer of cowpea in Brazil. However, due to the low technological level employed by the region's producers, the productivity achieved is far below that of other producing regions in the country. The choice of adapted cultivars, with greater productive potential, associated with the use of low-cost technologies, such as the use of high efficiency diazotrophic bacteria strains in the biological fixation of nitrogen are the main advances for the production of cowpea beans in the region. However, there are still few studies evaluating the performance of improved cultivars associated with rhizobic inoculation strains in the Brazilian semiarid region. Thus, in order to evaluate the agronomic efficiency of cultivars beans inoculated with rhizobics recommended for culture in a semi-arid environment, field experiments were conducted in two agricultural crops in Mossoró-RN, the first crop from January to April 2019, and the second from June to August 2019. The experimental design adopted was that of randomized blocks, arranged in a 4 x 4 factorial scheme, and the treatments were composed of four improved cultivars of cowpea-beans: BRS Imponente, BRS Itaim, BRS Novaera and BRS Tumucumaque; and four sources of N, being two strains of Bradyrhizobium spp. registered for the culture (BR 3262 and BR 3267), mineral N application (50 kg ha-1) and one absolute control, without inoculation and without mineral N application. The plots were made up of four planting rows 4 m long. The spacing adopted was 0.50 m between rows and 0.20 m between pits in the same row, with two plants per pit, resulting in a population density of 200,000 ha-1 plants. At 40 DAP, eight plants were collected from the useful area of each plot and were evaluated the number and dry matter of nodules; dry matter of the aerial part and relative efficiency of nodulation. From one of the lines of the useful area of each plot the length of green pods, number of grains per green pod, weight of 100 green grains, productivity of green grains and index of green grains were evaluated. From the other line of the useful area the length of dry pods, number of grains per dry pod, weight of 100 dry grains, dry grain productivity and dry grain index were evaluated. The rhizobium strains promoted an increase in the nodulation of the cowpea cultivars. The BRS Tumucumaque cultivar presented greater productive potential of green and dry grains. The inoculation of cowpea-bean seeds with BR 3262 and BR 3267 of Bradyrhizobium spp. was able to provide a yield of green grains similar to that obtained with mineral fertilization application of N